Evaluate: (-2y)/(3)-(2y)/(6)=4

Expression: $\frac{ -2y }{ 3 }-\frac{ 2y }{ 6 }=4$

Rewrite the equation in slope-intercept form


A term with $x$ is missing, which means that this term has the coefficient $0$


Subtracting is the same as adding the opposite

$y=0x+\left( -4 \right)$

Since the equation is written in slope-intercept form, $y=mx+b$, identify the slope of the line as the coefficient next to the variable $x$

$\begin{array} { l }y=0x+\left( -4 \right),& m=0\end{array}$

Identify the $y$-intercept of the line as the constant term

$\begin{array} { l }y=0x+\left( -4 \right),& m=0,& b=-4\end{array}$

The slope of the line is $m=0$ and the $y$-intercept is $b=-4$

$\begin{array} { l }m=0,& b=-4\end{array}$